Evaluation of fermentation performance of yeast strains isolated from Passiflora ligularis - Shuqing Feng; Qin Zhu; Jian Cai; Qingfang Xu; Jie Li; Qian Sun; Ying Mao; Ling Zhu (Archives of Microbiology, 2026)

Optimizing fertilizer and planting density to stabilize yields and improve water use efficiency in rain-fed wheat–maize rotations - Xueni Yang; Shujie Sun; Haocong Li; Ziyan Guo; Chi Ma; Bo Liu; Wei Zhang; Ruixia Ding; Peng Zhang; Tiening Liu; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2026)

The damaging effects of polyethylene microplastics exposure on juvenile carp and the ameliorative role of Opuntia Milpa alta extract - Yu Sun; Qiurong Zhang; Qingfang Deng; Nima Bai; Huaguo Chen (ENGINEERING Environment, 2026)

Correction: Sun et al. Tectonic Controls on Late Paleozoic Shale Gas Preservation in Western Shandong, China. J. Mar. Sci. Eng. 2025, 13, 1121 - Jing Sun; Yuting Zhao; Jie Liang; Xiujuan Zhang; Qingfang Zhao (Journal of Marine Science and Engineering, 2025)
Error in Figure/Table [...]

Thermal p-n junctions: a macroscopic thermal diode based on heterogeneous materials - Yue Zhang; Baotong Li; Pengfei Sun; Yu Hou; Jun Hong; Meng Shi; Liang Zeng; Qingfang Liu (Chemical Engineering Journal, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Organic matter accelerated microbial iron reduction and available phosphorus release in reflooded paddy soils - Xipeng Liu; Yuchen Shu; Kejie Li; Haotian Wang; Qingfang Bi; Haibo Wang; Chengliang Sun; Xianyong Lin (Soil Ecology Letters, 2025)

Tectonic Controls on Late Paleozoic Shale Gas Preservation in Western Shandong, China - Jing Sun; Yuting Zhao; Jie Liang; Xiujuan Zhang; Qingfang Zhao (Journal of Marine Science and Engineering, 2025)
Based on structural geology, petrology, shale gas geology, and basin modeling, this study investigates the characteristics of tectonic evolution and sedimentary responses in Western Shandong since the Late Paleozoic. Additionally, this study systematically investigates the hydrocarbon generation and reservoir formation conditions of Late Paleozoic shale gas and analyzes the controlling effects of tectonic activities on shale gas preservation. It is concluded that the TOC of the Late Paleozoic source rocks in this area ranges from 1.0% to 4.5%, considered as moderate to good source rocks. The Ro ranges from 0.7% to 3.5%, indicating a low to overmature stage. Deep concave source rocks have strong hydrocarbon generation potential. The Late Paleozoic shale gas reservoirs in Western Shandong are affected by superposed multiphase tectonic movements, where the activity of fault systems exerts dual controls on shale gas preservation.

Decoding the aroma changes of stir-fried shredded potatoes with different soy sauces using thermal desorption combined with gas chromatography–mass spectrometry and sensory evaluation - Ruixin Meng; Dandan Pu; Zikang Xu; Jinchang Liu; Qingfang Zhang; Maosheng Xu; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2025)

Transcriptome analysis of human spermatozoa with different DNA fragmentation index using RNA sequencing - Kailin Yang; Xue Sun; Qiyuan Zheng; Chen Pan; Siyuan Wang; Qingfang Lu; Changlong Xu; Yangqing Lu (Reproductive Biology, 2024)

Fault Characteristics and Reservoir Potential of Mesozoic Basins in the Southern East China Sea - Yanqiu Yang; Chuansheng Yang; Jing Sun; Jie Liang; Qingfang Zhao; Jianqiang Wang (Journal of Marine Science and Engineering, 2024)
The East China Sea Basin (ECSB) is an integral part of the Western Pacific tectonic system. Its development is linked to the Kula–Pacific Plate and the formation and expansion of the Philippine Sea Basin. Recent advancements in exploration technologies and theory have been applied to Mesozoic basins in the East China Sea. Researchers have posited that the southern basin has great oil and gas exploration potential. However, the characteristics and evolution of fault structures and their influence on hydrocarbon accumulation remain unclear. Here, in-depth geometric and kinematic analyses of Mesozoic fault structures in the southern ECSB were conducted using the latest interpretations of 2D seismic data and structural analysis theory. The findings revealed that the fault system was well developed and predominantly exhibited multiphase extensional and extensional-torsional features. Based on their lateral distribution and morphology, faults were categorized into three structural styles and seven combinations. According to their developmental timing, periods of active faulting were attributed to the Yanshan and Himalayan epochs. Multiphase fault activities strongly controlled the formation of traps and thus hydrocarbon accumulation, while earlier NE-trending faults controlled the formation of structural belts and hydrocarbon source areas.

The Volcanic Rocks and Hydrocarbon Accumulation in the Offshore Indus Basin, Pakistan - Jing Sun; Jie Liang; Jianming Gong; Jing Liao; Qingfang Zhao; Chen Zhao (Journal of Marine Science and Engineering, 2024)
To analyze the impact of volcanic rocks in the Offshore Indus Basin on hydrocarbon reservoir formation, seismic data interpretation, seismic data inversion, and sea–land correlation analysis were carried out. The results show that, longitudinally, volcanic rocks are mainly distributed at the top of the Cretaceous system or at the bottom of the Paleocene, and carbonate rock platforms or reefs of the Paleocene–Eocene are usually developed on them. On the plane, volcanic rocks are mainly distributed on the Saurashtra High in the southeastern part of the basin. In terms of thickness, the volcanic rocks revealed by drilling in Karachi nearshore are about 70 m thick. We conducted sparse spike inversion for acoustic impedance in the volcanic rock area. The results show that the thickness of the Deccan volcanic rocks in the study area is between 250 and 750 m which is thinning from southeast to northwest. Based on sea–land comparison and comprehensive research, the distribution of volcanic rocks in the Indian Fan Offshore Basin played a constructive role in the Mesozoic oil and gas accumulation in the Indus offshore. Therefore, in the Indian Fan Offshore Basin, attention should be paid to finding Mesozoic self-generated and self-stored hydrocarbon reservoirs and Cenozoic lower-generated and upper-stored hydrocarbon reservoirs.

Harmful effects of microplastics on respiratory system of aquatic animals: A systematic review and meta-analysis - Qiurong Zhang; Xin Zhou; Yu Sun; Qingfang Deng; Qing Wu; Zhirui Wen; Huaguo Chen (Aquatic Toxicology, 2024)

Exosomes from porcine serum as endogenous additive maintain function of boar sperm during liquid preservation at 17 °C in vitro - Yang Wang; Qimin Liu; Qingfang Sun; Lijuan Zheng; Tianqi Jin; Heran Cao; Chao Zhu; Long Li; Ye Gong; Fangxia Yang; Wuzi Dong (Theriogenology, 2024)

Hazards of microplastics exposure to liver function in fishes: A systematic review and meta-analysis - Yu Sun; Qingfang Deng; Qiurong Zhang; Xin Zhou; Ruhai Chen; Siyu Li; Qing Wu; Huaguo Chen (Marine Environmental Research, 2024)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Testicular miRNAs and tsRNAs provide insight into gene regulation during overwintering and reproduction of Onychostoma macrolepis - Guofan Peng; Chao Zhu; Qingfang Sun; Jincan Li; Yining Chen; Yingjie Guo; Hong Ji; Fangxia Yang; Wuzi Dong (Fish Physiology and Biochemistry, 2022)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Tanning performance and environmental effects of nanosized graphene oxide tanning agent - Shenghua Lv; Qingfang Zhou; Ying Li; Yaya He; Haoran Zhao; Shiyu Sun (Clean Technologies and Environmental Policy, 2016)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Determination of zinc contents in rabbits with cerebral ischemia by NAA and ICP-AES - Yinsong Wang; Huifang Zhao; Tianxi Zhang; Mingguang Tan; Guisun Zhuang; Baolin Chen; Zongzhi Huang; Hengli Tian; Qingfang Sun (Biological Trace Element Research, 1999)